The Role of Audit Fees in Moderating the Impact of Competency and Professionalism on Audit Quality - Lubis, Henny Zurika; Siregar, Nadia Prastika (AIBPM Publisher, 2024)
Audit quality is an important aspect that is influenced by various factors, both internal and external auditors. Factors such as competence, independence, ethics, and professional concerns in auditors significantly impact audit quality. This study aims to determine the influence of auditor competence and professionalism on audit quality with audit fees as a moderating variable. The research method used is associative research, which tests the influence between variables. Data was obtained by distributing questionnaires to respondents, namely auditors who work at Public Accounting Firms in Medan City. Furthermore, the data was analyzed using descriptive analysis, multiple regression analysis test, classical assumption test, hypothesis test, and moderated regression analysis. This study's results show that auditors' competence and professionalism significantly affect audit quality, and audit fees cannot moderate the relationship between auditor competence and professionalism and audit quality